Genetic Generalized Epilepsy and Intrafamilial Phenotypic Variability with Distal 7q11.23 Deletion. (April 2022) - Birca, Veronica; Myers, Kenneth A.
Background: Distal 7q11.23 deletions are variably associated with epilepsy, intellectual disability and neurobehavioural abnormalities. The relative importance of different genes in this region in contributing to different phenotypes is not clear, though HIP1 and YWHAG are both thought to play important roles.Patients and Methods: We performed thorough phenotyping on members of a family in which multiple members carried a relatively small 0.8 Mb distal 7q11.23 deletion, affecting 17 genes.Results: Two brothers and a half-brother had all inherited the 7q11.23 deletion from their mother. The eldest two both had global developmental impairment and genetic generalized epilepsy, involving absence, myoclonic or myoclonic-atonic seizures. There was no history of seizures in the mother or her youngest son, but both also had developmental impairment.Conclusion: Distal 7q11.23 deletions affecting HIP1 and YWHAG may cause developmental impairment and genetic generalized epilepsy, with considerable intrafamilial phenotypic variability.